Equações preditivas para as pressões respiratórias máximas de crianças brasileiras - Borja, Raissa de Oliveira (2011)
I ntroduction: The assessment of respiratory muscle strength is important in the diagnosis and monitoring of the respiratory muscles weakness of respiratory and neuromuscular diseases. However, there are still no studies that provide predictive equations and reference values for maximal respiratory pressures for children in our population. Aim: The purpose of this study was to propose predictive equations for maximal respiratory pressures in healthy school children. Method: This is an observational cross-sectional study. 144 healthy children were assessed. They were students from public and private schools in the city of Natal /RN (63 boys and 81 girls), subdivided in age groups of 7-8 and 9-11 years. The students presented the BMI, for age and sex, between 5 and 85 percentile. Maximal respiratory pressures were measured with the digital manometer MVD300 (Globalmed ®). The maximal inspiratory pressure (MIP) and maximal expiratory pressures (MEP) were measured from residual volume and total lung capacity, respectively. The data were analyzed using the SPSS Statistics 15.0 software (Statistical Package for Social Science) by assigning the significance level of 5%. Descriptive analysis was expressed as mean and standard deviation. T'Student test was used for unpaired comparison of averages of the variables. The comparison of measurements obtained with the predicted values in previous studies was performed using the paired t'Student test. The Pearson correlation test was used to verify the correlation of MRP's with the independent variables (age, sex, weight and height). For the equations analysis the stepwise linear regression was used. Results: By analyzing the data, we observed that in the age range studied MIP was significantly higher in boys. The MEP did not differ between boys and girls aged 7 to 8 years, the reverse occurred in the age between 9 and 11 years. The boys had a significant increase in respiratory muscle strength with advancing age. Regardless sex and age, MEP was always higher than the MIP. The reference values found in this study are similar to a sample of Spanish and Canadian children. The two models proposed in previous studies with children from other countries were not able to consistently predict the values observed in this studied population. The variables sex, age and weight correlated with MIP, whereas the MEP was also correlated with height. However, in the regression models proposed in this study, only gender and age were kept exerting influence on the variability of maximal inspiratory and expiratory pressures. Conclusion: This study provides reference values, lower limits of normality and proposes two models that allow predicting, through the independent variables, sex and age, the value of maximal static respiratory pressures in healthy children aged between 7 and 11 years old